(untitled) (Bangladesh Journal of Agricultural Research, 2010)
Field experiments were carried out during rabi (winter) seasons of 2004-2005 and 2005-2006 at the Bangladesh Agricultural Research Institute Farm, Gazipur to determine the effects of seeds collected from different plant parts on nitrogen content and nitrogen uptake, protein content, and protein yield of lentil. Lentil seeds were collected from different parts of lentil plants viz. i) seeds collected from upper parts (P1), ii) seeds collected from middle parts (P2), and iii) seeds collected from lower parts of lentil plants (P3). Significant variation among the three test varieties of lentil was observed for nitrogen content and nitrogen uptake, and protein content where the highest concentration of nitrogen was observed in BARI Masur-4 which ultimately gave higher protein yield, while the lowest was in BARI Masur-2. Seeds collected from different plant parts had significant effect for nitrogen and protein content where P3 site recorded the highest results. BARI Masur-2 seeds collected from lower parts of lentil recorded higher N content and protein content but BARI Masur-4 seeds collected from lower parts or BARI Masur-3 seeds collected from middle parts gave higher N uptake and protein yield. Keywords: Lentil; nitrogen uptake; protein yield. DOI: 10.3329/bjar.v35i3.6458 Bangladesh J. Agril. Res. 35(3) : 515-523